2013
DOI: 10.1089/lrb.2012.0020
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Precision of Dual Energy X-Ray Absorptiometry and Bioelectric Impedance Spectroscopy in the Assessment of Breast Cancer-Related Lymphedema

Abstract: For BCRL, these findings suggest that DXA and BIS are two measurement instruments that provide acceptable levels of precision for the measurement of arm lean mass, fat mass and ECF volume, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Bioimpedance analysis demonstrates excellent interrater and intrarater reliability (0.95 and 0.99, respectively) and highly reproducible measures (covariance = 0.2%-0.268%) in research models 42–44. Newman et al45 found that BIA has the precision capable of detecting (1.65%-1.86%) the onset of extracellular fluid accumulation indicative of early development of lymphedema. Test-retest reliability using the Imp XCA analyzer, a clinical BIA device, demonstrates strong agreement in the healthy and at-risk groups (ICC = 0.99) but only fair agreement in the group with known breast cancer–related lymphedema (ICC = 0.69) 41.…”
Section: Bioimpedance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bioimpedance analysis demonstrates excellent interrater and intrarater reliability (0.95 and 0.99, respectively) and highly reproducible measures (covariance = 0.2%-0.268%) in research models 42–44. Newman et al45 found that BIA has the precision capable of detecting (1.65%-1.86%) the onset of extracellular fluid accumulation indicative of early development of lymphedema. Test-retest reliability using the Imp XCA analyzer, a clinical BIA device, demonstrates strong agreement in the healthy and at-risk groups (ICC = 0.99) but only fair agreement in the group with known breast cancer–related lymphedema (ICC = 0.69) 41.…”
Section: Bioimpedance Analysismentioning
confidence: 99%
“…Newman et al45 measured the affected and nonaffected arms of patients with breast cancer–related lymphedema and noted a significant difference in fat and lean mass (increase in both by 15%, P < .0001) but only a 0.6% change in bone mass. The interrater reliability of DXA to measure arm volumes was excellent (ICC = 0.99) 63.…”
Section: Other Diagnostic Measuresmentioning
confidence: 99%
“…DEXA scans measure fat, lean muscle, and bone mineral content in the region of interest extending from the glenohumeral joint to the fingertips. A recent study found that DEXA was superior to circumferential measurements and water displacement with respect to the reproducibility of measurements of the affected and contralateral arms [27]. Skin viscoelasticity and dual-beam absorptiometry are other techniques used for detection of LE [28,29].…”
Section: Soft Tissue Imagingmentioning
confidence: 99%
“…Several studies by Ward and colleagues have established impedance ratio ranges for lymphedema diagnosis (99, 101, 102), while Kilbreath et al demonstrated that comparing the postoperative change in extracellular fluid volume of the ipsilateral extremity to a preoperative baseline may provide a more effective diagnosis of edema than comparison to reported thresholds (103). Newman and colleagues demonstrated that bioimpedance spectroscopy has sufficient sensitivity to assess not only extracellular fluid volume, but also lean mass and fat mass between affected and unaffected extremities of Stage II unilateral breast cancer-related lymphedema patients, which could provide additional diagnostically-relevant metrics to monitor the progression of later-stage lymphedema (104). Most recently, and arguably most excitingly, Ridner et al recently developed and reported the first self-measurement protocol for bioimpedance testing, which may pave the way for a home-use diagnostic in the future (105).…”
Section: Interstitial Changesmentioning
confidence: 99%